A Concise Note on the Theory of Two Truths in Buddhism - Tashi Dorjey (Soshum: Jurnal Sosial dan Humaniora, 2018)
The concept of two truths in the Theravāda Buddhism is found in Saṅgīti Sutta of the Dῑghanikāya, where the four kinds of knowledge are enumerated. “Knowledge to wit: knowledge of the Doctrine, knowledge in its corollaries, knowledge of what is in another’s consciousness and popular knowledge”. The latter two types of knowledge refer to the concept of two truths in Theravāda Buddhism. In the history of Mahāyāna Buddhism, there are four philosophical systems in Buddhist thoughts, viz. the Vaibhāṣika School, the Sautāntrika School, the Yogācāra/Cittamatra, and the Madhyamaka School. According to Vaibhāṣikas, it is claimed that wholes and continua which are reducible are to be known as conventional truth, while the atoms and point-instant consciousness which are irreducible is to be known as the ultimate truth. In terms of the Sautrāntika, they formulated the principle of two truths in such a way that workability phenomenon is recognized as the ultimate truth and the phenomenon which is not workability is to be understood as conventional truth. In accordance with Yogācāras, being an idealist, they propose that all physical objects are just mental construction and they are unreal. They are to be known as conventional truth, whereas the ultimate reality is pure consciousness. It is the perfect nature of the things and it is ultimate truths. According to Mādhyamaka, the conventional illusory mode of appearance which is in disagreement with their mode of existence is known as conventional truth and its mode of appearance is in agreement with its mode of existence is known as ultimate truth.